Native Huts, Trinidad - Briant (My University, 2010)
Postcard from the past features about a dozen mud huts made from tapia which is a mixture of clay, grass, cow dung and water while the roofs are made from carat palm leaves. Printed on the reverse side of the postcard is “British manufacture throughout.”
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Huts--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Housing, Rural--Trinidad and Tobago; Thatched roofs--Trinidad and Tobago; Communities--Trinidad and Tobago; Ajoupa